PERMINTAKATAN LAHAN IRIGASI UNTUK MENEKAN KONVERSI PENGGUNAAN LAHAN DI DAERAH IRIGASI BENDUNG COLO KABUPATEN SUKOHARJO - , Rochmat Martanto, Prof. Dr. Ir. Sahid Susanto, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was conducted in the irrigation area of Bendung Colo (Colo Weir) in the Municipality of Sukoharjo (Kabupaten Sukoharjo), which comprise many potentials for land use conversion. The objectives of this research wereto